EKSEKUSI PUTUSAN PIDANA PENJARA TERHADAP ANAK YANG TELAH MELAMPAUI BATAS USIA 18 TAHUN DALAM PERSPEKTIF SISTEM PERADILAN PIDANA ANAK - Nila Wahyuningtyas Wardani; Eka Nanda Ravizki (Jurnal Ilmiah Advokasi, 2025)
This study analyzes the issues surrounding the execution of imprisonment sentences against offenders who have exceeded the age of 18 within the framework of the Juvenile Criminal Justice System (SPPA), referring to Decision Number 2818 K/PID.SUS/2024. The problem arises at the stage of executing the court decision when the convicted individual has surpassed the age of 18, resulting in administrative and legal obstacles concerning placement in a Special Child Development Institution (LPKA). The refusal of admission by the LPKA places the prosecutor, as the executing authority, in a dilemma between enforcing the court’s ruling and complying with statutory regulations. This research employs an empirical juridical method with statutory and case approaches, supported by field data on the practical implementation of court decisions. The findings indicate a lack of judicial precision in determining the appropriate correctional placement, as normatively, individuals who have exceeded the age of 18 should be placed in a Youth Correctional Institution. This condition reflects a lack of synchronization between the operative part of the judgment and the provisions of the SPPA, resulting in legal uncertainty during the execution stage. Greater judicial accuracy and regulatory harmonization are required to ensure legal certainty and the protection of children's rights within the criminal justice system.Keywords: Execution of Judgment; Juvenile Offender; Juvenile Criminal Justice System; Legal Certainty